2020
DOI: 10.1155/2020/2641461
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Hyperoxia Downregulates Claudin-4, Occludin, and ZO-1 Expression in Rat Kidney Accompanied by Impaired Proximal Tubular Development

Abstract: Hyperoxia is essential to manage in preterm infants but causes injury to immature kidney. Previous study indicates that hyperoxia causes oxidative damage to neonatal kidney and impairs renal development. However, the underlying mechanisms by which neonatal hyperoxia effects on immature kidney still need to be elucidated. Tight junction, among which the representative proteins are claudin-4, occludin, and ZO-1, plays a crucial role in nephrogenesis and maintaining renal function. Inflammatory cytokines are invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Tubular damage rate, which is one of the histopathological findings of the hyperoxia effect in our study (Figs. 1, 2 and 3), was also shown in some studies in the literature [2,[27][28][29] in neonatal rat kidneys, but unlike these studies, we preferred adult rats in our study. Xu et al stated that inhibited expression of tight junction proteins (claudin-4, occludin, and ZO-1) in proximal tubules might be a potential mechanism of neonatal hyperoxia-induced nephrogenic disorders [28].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Tubular damage rate, which is one of the histopathological findings of the hyperoxia effect in our study (Figs. 1, 2 and 3), was also shown in some studies in the literature [2,[27][28][29] in neonatal rat kidneys, but unlike these studies, we preferred adult rats in our study. Xu et al stated that inhibited expression of tight junction proteins (claudin-4, occludin, and ZO-1) in proximal tubules might be a potential mechanism of neonatal hyperoxia-induced nephrogenic disorders [28].…”
Section: Discussionmentioning
confidence: 74%
“…1, 2 and 3), was also shown in some studies in the literature [2,[27][28][29] in neonatal rat kidneys, but unlike these studies, we preferred adult rats in our study. Xu et al stated that inhibited expression of tight junction proteins (claudin-4, occludin, and ZO-1) in proximal tubules might be a potential mechanism of neonatal hyperoxia-induced nephrogenic disorders [28]. In the analysis of the histopathological findings of our study, we see that the state of hyperoxia causes glomerular and tubular damage due to increased oxidative stress, and this damage rate does not improve much with the use of tadalafil (Tables 2 and 3).…”
Section: Discussionmentioning
confidence: 74%
“…44 An additional study suggested that the mechanism of hyperoxic nephropathy may be related to impaired tight junction proteins in the kidney, and that neonatal hyperoxia extensively inhibits the expression of tight junction proteins during proximal tubule development, possibly by downregulating proximal tubule claudin-4 expression and perhaps mediated through IL-6 and TNF-α; however, the inhibition of expression mediated by IL-6 and TNF-α are only involved in hyperoxia-induced renal damage and are not dependent on their proinflammatory effects. 45 Moreover, a mouse model study found no change in the number of kidney units in mice exposed to 65% oxygen 18 and no significant long-term deleterious effects on glomerular structure. Conversely, early exposure to 80% oxygen resulted in hypertension, changes in vascular function, and reduced kidney unit function in adulthood.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Although prior work has focused primarily on the role of ZO-1 in slit diaphragm, it has been demonstrated that ZO-1 is also abundantly expressed in renal tubule epithelial cells [108,119,120]. The ZO-1/ZONAB signal pathway is indispensable for modulating epithelial phenotype.…”
Section: Zo-1mentioning
confidence: 99%